1986
DOI: 10.1213/00000539-198606000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Gas Exchange during Controlled Ventilation in Children with Normal and Abnormal Pulmonary Circulation

Abstract: R, NIKLASSON L, DREFELDT B. Gas exchange during controlled ventilation in children with normal and abnormal pulmonary circulation: a study using the single breath test for carbon dioxide. Anesth Analg 1986;65:645-52. Carbon dioxide single breath tests (SBT-COJ were obtained during anesthesia and controlled ventilation in 42 children about to undergo thoracic surgery. The tests were obtained with a computerized system based on the Servo ventilator. The system made on-line corrections for compressed volume, appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 0 publications
2
29
2
Order By: Relevance
“…Vd/Vt was lower in the BTS group when compared with that in the RV-PA group at all time points. Fletcher et al (9) reported high Vd/Vt (0.41) in patients with pulmonary hypoperfusion. Although Vd/Vt values decreased over the early postoperative period, a large difference in arterial to end-tidal CO 2 (thus Vd/Vt) remained at the time of extubation from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Vd/Vt was lower in the BTS group when compared with that in the RV-PA group at all time points. Fletcher et al (9) reported high Vd/Vt (0.41) in patients with pulmonary hypoperfusion. Although Vd/Vt values decreased over the early postoperative period, a large difference in arterial to end-tidal CO 2 (thus Vd/Vt) remained at the time of extubation from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 98%
“…Vd/Vt is increased in parenchymal lung disease and in diseases that alter lung perfusion. Children with congenital heart disease (CHD) characterized by either pulmonary hypoperfusion or cyanosis have been shown to have higher Vd/Vt, and higher Vd/Vt has been shown to prolong duration of mechanical ventilation and length of hospitalization after cardiac surgery for CHD (9,10). Children with congenital heart disease (CHD) characterized by either pulmonary hypoperfusion or cyanosis have been shown to have higher Vd/Vt, and higher Vd/Vt has been shown to prolong duration of mechanical ventilation and length of hospitalization after cardiac surgery for CHD (9,10).…”
mentioning
confidence: 99%
“…However, in patients with CHD, there exist large gradients between the PaCO 2 and the end-tidal exhaled alveolar gas carbon-dioxide (P ET CO 2 ). [2,3] In patients with cyanotic CHD, the difference is related to both increases in dead space ventilation and intracardiac venous admixture, whereas in patients with acyanotic CHD, the PAH resulting from the increased pulmonary blood flow may cause a greater ventilation perfusion mismatch resulting in increased PaCO 2 -P ET CO 2 gradients. [4] This difference may be further exaggerated in anesthetized and paralyzed patients with PAH due to atelectasis and increase in dead space ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore patients undergoing this procedure are frequently premature, ventilator‐dependent neonates in whom there is an increase in pulmonary relative to systemic blood flow. This causes increased lung water with a consequent decrease in lung compliance ( 74) and impaired V/Q matching ( 75). Surgical access is through a left thoracotomy, and the duct can normally be visualized with minimal lung retraction.…”
Section: Implications Of Specific Diagnoses or Surgical Proceduresmentioning
confidence: 99%